Effects of a Kundalini Yoga programme on cardiorespiratory fitness and health-related quality of life in university students - Antonio Eduardo López-Fuenzalida; Pablo Valdés-Badilla; Ludmila Varas-Yupátova; Pía Moya-Sauer; Clara Romero-Guastavino; Monserrat Zepeda-Díaz; Eduardo Báez-SanMartín (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Physical inactivity and sedentary behaviour are significant risk factors for diseases such as cardiovascular disease, cancer, and mental health disorders. Kundalini Yoga (KY) is recognised for its potential to improve physical and mental health.